The 3′-Untranslated Region of Hepatitis C Virus RNA Enhances Translation from an Internal Ribosomal Entry Site - Ito, Takayoshi (American Society for Microbiology, 1998)
Translation of most eukaryotic mRNAs and many viral RNAs is enhanced by their poly(A) tails. Hepatitis C virus (HCV) contains a positive-stranded RNA genome which does not have a poly(A) tail but has a stretch of 98 nucleotides (X region) at the 3′-untranslated region (UTR), which assumes a highly conserved stem-loop structure. This X region binds a polypyrimidine tract-binding protein (PTB), which also binds to the internal ribosome entry site (IRES) in HCV 5′-UTR. These RNA-protein interactions may regulate its translation. We generated a set of HCV RNAs differing only in their 3′-UTRs and compared their translation efficiencies. HCV RNA containing the X region was translated three- to fivefold more than the corresponding RNAs without this region. Mutations that abolished PTB binding in the X region reduced, but did not completely abolish, enhancement in translation. The X region also enhanced translation from another unrelated IRES (from encephalomyocarditis virus RNA), but did not affect the 5′-end-dependent translation of globin mRNA in either monocistronic or bicistronic RNAs. It did not appear to affect RNA stability. The free X region added in trans, however, did not enhance translation, indicating that the translational enhancement by the X region occurs only in cis. These results demonstrate that the highly conserved 3′ end of HCV RNA provides a novel mechanism for enhancement of HCV translation and may offer a target for antiviral agents.